Effects Of Atrial Natriuretic Peptide And Pregnancy On The Central And Peripheral Regulation Of The Cardiovascular Functions - Yusoff, Nurul Hasnida Mohammad (2010)
The present study focuses on two topics that are related to volume expansion (VE); investigating the effect of atrial natriuretic peptide (ANP) and pregnancy-induced changes, in the regulation of the cardiovascular functions. ANP is released from the cardiac atria in response to hypervolemic state. Even though its role during VE is well established, the central mechanism underlying its systemic effect is less studied. Therefore, this study sets out to examine the systemic and central effect of ANP, as well as the involvement of supraspinal vasopressin pathways in mediating the effect produced by intravenous ANP. Our findings show that the systemic administration of low and high doses of ANP in urethane-anaesthetized male Sprague-Dawley rats produce a significant renal sympathoinhibition, vasodilation and bradycardia, and these effects are dependent on the efficacy of a well established supraspinal vasopressin pathway.